The Remembered Land : Surviving Sea-Level Rise after the Last Ice Age - Leary, Jim (Debates in Archaeology Ser, 2015)
FC -- Half Title -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgements -- Part One: To Begin -- 1. Recognizing Northsealand -- Part Two: Landscape -- 2. Thinking the Imagined Land -- 3. The People of Northsealand -- 4. Shaping the World with Ice and Sea -- Part Three: Effects -- 5. Changing Worlds -- 6. Losing Place -- Part Four: Responses -- 8. Knowledge, Networks and Social Memory -- 9. Being Pragmatic -- Part Five: To End -- 10. The Remembered Land -- Epilogue -- Notes -- Index.